Construct Validity of the EuroQoL–5 Dimension and the Health Utilities Index in Head and Neck Cancer. (27th July 2021) - Noel, Christopher W.; Keshavarzi, Sareh; Forner, David; Stephens, Robert F.; Watson, Erin; Monteiro, Eric; Hosni, Ali; Hansen, Aaron; Goldstein, David P.; de Almeida, John R.
Abstract : Objective: The objective of this study was to evaluate the construct validity of 2 health utility instruments—the EuroQoL–5 Dimension (EQ‐5D) and the Health Utilities Index–Mark 3 (HUI‐3)—and to compare them with disease‐specific measures in patients with head and neck cancer. Study Design: Prospective cross‐sectional analysis. Setting: Princess Margaret Cancer Centre. Methods: Patients were administered the EQ‐5D, HUI‐3, the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ‐C30) and its head and neck cancer module (EORTC QLQ‐H&N35), and the University of Washington Quality of Life Questionnaire (UWQoL). Several a priori expected relations were examined. The correlative and discriminative properties of the various instruments were examined. Results: A total of 209 patients completed the 4 questionnaires. A significant ceiling effect was observed among EQ‐5D responses (23% reported a maximum score of 1). The EQ‐5D (rho = 0.79) and HUI‐3 (rho = 0.60) had a strong correlation with the social‐emotional domain of the UWQoL. The EQ‐5D had a moderate correlation with the physical domain of the UWQoL (rho = 0.42), whereas the HUI‐3 had a weak correlation (rho = 0.29). The EQ‐5D and HUI‐3 were able to distinguish among levels of health severity measured on the EORTC QLQ‐C30 though not the QLQ‐H&N35. Comparatively, the UWQoL was able to distinguish levels of disease severity on the EORTC QLQ‐C30 and QLQ‐H&N35. Conclusion: The results of this study demonstrate that disease‐specific domains from head and neck quality‐of‐life instruments are not strongly correlated with the EQ‐5D and HUI‐3. Consideration should be put toward development of a disease‐specific preference‐based measure for health economic evaluation. Level of evidence: 4.